Physical Performance and Clinical Outcomes in Dialysis Patients: A Secondary Analysis of the Excite Trial - Claudia Torino; Fabio Manfredini; Davide Bolignano; Filippo Aucella; Rossella Baggetta; Antonio Barillà; Yuri Battaglia; Silvio Bertoli; Graziella Bonanno; Pietro Castellino; Daniele Ciurlino; Adamasco Cupisti; et al. (Karger Publishers, 2014)
Background/Aims: Scarce physical activity predicts shorter survival in dialysis patients. However, the relationship between physical (motor) fitness and clinical outcomes has never been tested in these patients. Methods: We tested the predictive power of an established metric of motor fitness, the Six-Minute Walking Test (6MWT), for death, cardiovascular events and hospitalization in 296 dialysis patients who took part in the trial EXCITE (ClinicalTrials.gov Identifier: NCT01255969). Results: During follow up 69 patients died, 90 had fatal and non-fatal cardiovascular events, 159 were hospitalized and 182 patients had the composite outcome. In multivariate Cox models - including the study allocation arm and classical and non-classical risk factors - an increase of 20 walked metres during the 6MWT was associated to a 6% reduction of the risk for the composite end-point (P=0.001) and a similar relationship existed between the 6MWT, mortality (PConclusions: Poor physical performance predicts a high risk of mortality, cardiovascular events and hospitalizations in dialysis patients. Future studies, including phase-2 EXCITE, will assess whether improving motor fitness may translate into better clinical outcomes in this high risk population.